Dominica : Staff Report for the 2002 Article IV Consultation and Request for Stand-By Arrangement. (IMF Staff Country Reports; Country Report, 2002)
This paper examines Dominica's 2002 Article IV Consultation and a Request for Stand-By Arrangement (SBA). The authorities' program for 2002/03, for which support through a one-year SBA is being requested, is aimed at restoring order to the public finances and relaxing the cash constraint to protect essential public expenditure and reduce public debt to the banking system. The IMF staff is of the view that the authorities' economic program is consistent with the objective of laying a basis for sustained growth of output and employment over the medium term.